Note on the q-Extension of Barnes' Type Multiple Euler Polynomials - Leechae Jang; Taekyun Kim; Young-Hee Kim; Kyung-Won Hwang (Journal of Inequalities and Applications, 2009)
We construct the q-Euler numbers and polynomials of higher order, which are related to Barnes' type multiple Euler polynomials. We also derive many properties and formulae for our q-Euler polynomials of higher order by using the multiple integral equations on ℤp.